Factors influencing takaful products acceptance among executive-level workers in CMA CGM Malaysia Sendirian Berhad (I-City Branch) - Teoh, Kuih See (2017)
The purpose of the study is to investigate the factors of network expansion of agency distribution, awareness of consumers about takaful, consumers switching behaviour and product innovation influencing takaful products acceptance among executive-level workers in CMA CGM Malaysia Sendirian Berhad (I-city Branch). Quantitative research design that involved of questionnaire had been used in this study on testing factors influencing takaful products acceptance among executive-level workers in CMA CGM Malaysia Sendirian Berhad (I-city Branch). Simple random sampling method had been used in this study. Primary data were collected through series of questions in a questionnaire that were distributed among the executive-level workers in CMA CGM Malaysia Sendirian Berhad (I-city Branch). 80 sets of the questionnaire had been distributed and researcher got back 80 sets of the questionnaire. The response rate for this study was 100%. All the data collected from respondents were analysed based on the Statistical Package for Social Sciences (SPSS) Version 23 software. The data analysis involved both descriptive and inferential statistics. Besides that, correlation analysis and regression analysis had been used in this study. Findings indicated that there is no positive significant relationship between the factors of network expansion of agency distribution and consumer switching behaviour with takaful products acceptance among executive-level workers in CMA CGM Malaysia Sendirian Berhad (I-city Branch). On the other hand, findings shown that the factors of awareness of consumers about takaful and product innovation are having positive significant relationship with takaful products acceptance among executive-level workers in CMA CGM Malaysia Sendirian Berhad (I-city Branch). The findings of this research has become useful for takaful companies to focus and put more effort on the factors of awareness of consumers about takaful and product innovation in order to be successful in the insurance industry in the coming future.